Analyses of the mechanism and therapeutic targets of senescence related genes in ischemic stroke with multi-omics approach - Nanding Li; Shanquan Jing; Kang An; Bo Jia; Yingjie Han; Zan Wang; Chengcai Li; Xiaole Li; Jiwei Wang; Wei Liu; Conghui Li (Scientific Reports)
Abstract Ischemic stroke (IS) affects 11 million people annually, posing substantial clinical and economic burdens. Current therapies remain limited by time sensitivity and variable efficacy, necessitating novel biomarkers. We developed a multi-omics framework to investigate senescence-associated gene regulation in IS. After normalizing GSE22255 and GSE58294 datasets, we systematically identified aging-related differentially expressed genes (DEGs). Functional annotation via Gene Set Enrichment Analysis (GSEA) and machine learning-driven Weighted Gene Co-expression Network Analysis (WGCNA) identified core genetic signatures validated in the GSE16561 cohort. Key regulators underwent single-gene profiling, immune microenvironment evaluation, and transcriptional network analysis. Reverse transcription-quantitative PCR (RT-qPCR) confirmed bioinformatics findings. We identified 132 senescence-related DEGs, with PTGS2 emerging as a key biomarker. Pathway analyses revealed significant NF-κB, HIF-1, and TGF-β signaling pathway activation. CIBERSORT-based immune profiling showed altered lymphocyte/macrophage ratios in IS patients. Drug-gene interaction analysis identified nine therapeutic compounds, including etodolac targeting NFE2L2 and PTGS2. A strong positive correlation (r = 0.72, p < 0.001) between NFE2L2 and PTGS2 expression was observed. This study establishes senescence-related genes as promising biomarkers and therapeutic targets for IS, particularly through NFE2L2-PTGS2 interactions, providing a foundation for developing immunomodulatory and targeted therapies.